Infrared Video Thermometry Guidance for Surgical Correction of Chylothorax in Dogs - Ribeiro, Mariana da Silva; Junior, Marcelo Borges dos Santos; de Moraes, Marina Tomaz Gonçalves; Cabral, Paula Gebe Abreu; Antunes, Fernanda; Oliveira, André Lacerda de Abreu (Acta Scientiae Veterinariae, 2018)
Background: Macroscopic identification of the extravasation site of chyle in patients with chylothorax is a major challenge. Current forms of identification are invasive and/or expose patients to radiation, as in computerized tomography and radiography. A prototype device that uses infrared video thermometry images to detect temperature increments of 0.1ºC has been developed. This device can process and show real-time images or video on a monitor during surgeries. Therefore, the aim of this work was to report the first successful case in which this innovative device was tested in the transoperative period to identify the thoracic duct and its tributaries in a chylothorax surgery performed in a dog. Case: A 2-year-old male dog of the Shiba Inu breed was presented to the veterinary hospital with exercise intolerance, cough, emaciation, and no history of trauma. Clinical examination was performed along with complete blood count, biochemical analysis, and thoracic radiography. The patient exhibited dyspnea and had diminished breath sounds on chest auscultation. Radiographic images revealed moderate pleural effusion. The dog was anesthetized and submitted to thoracotomy, which enabled visualization of a chylous effusion. A sample of the effusion was collected for cytological and biochemical analyses. Subsequently, pericardiectomy was carried out, and identification of the thoracic duct and its tributaries was guided by an innovative device that generates infrared video thermometry images in real time. The extravasation site of the chyle was visualized on the images shown on a monitor. Consequently, after ligation of the tributary vessel, interruption of chyle overflow could be noticed on the monitor. Thoracotomy was routinely closed, and a drain was placed through an intercostal space after incision. Thirty days after the surgery, the dog exhibited no signs of recurrence. Cytological and biochemical analyses of the effusion revealed an abnormal transudate that had a density of 1,030 g/cm3, alkaline pH, predominance of neutrophils and lymphocytes, and high levels of proteins, triglycerides and cholesterol. These results indicated that the effusion analyzed was chyle. Discussion: Macroscopic aspects of an effusion alone should not be used to make a definitive diagnosis; cytological, physical, and biochemical evaluations are indispensable. The specimen analyzed had a higher concentration of triglycerides than blood, and its cholesterol concentration was lower than that found in blood. Findings like these have already been reported as indicative of chylous effusion. Thoracic duct ligation is the most used technique for correction of chylothorax, and is the technique with better outcomes. Thermometry has already been used for clinical examination in several diseases. However, the innovative device used in this study has the advantage of being noninvasive, and was able to guide the surgeon during the surgery to locate the thoracic duct and precisely identify the tributary lymphatic vessel responsible for the chylous effusion. The physical space occupied by the device did not disturb the surgical team since a small infrared image generator was placed one meter above the patient to take high definition images of the entire animal in the evaluation field. The thermometry device was very useful, non-invasive, and precise to differentiate thoracic structures and to identify the site of extravasation of chyle. It also allowed a more interactive and precise surgical approach by the surgical team, which was essential to the success of the surgery. Keywords: chyle extravasation, infrared diagnosis, surgery, thorax.